Does Islamic Social Reporting Enhance the Profitability of Islamic Banks? Evidence from Selected OIC Countries - Dian Fahmy Sidiq; Wahyudi, Rofiul; Mufti Alam Adha (Department of Islamic Financial Management, Faculty of Economics and Islamic Business, Sunan Kalijaga State Islamic University, Yogyakarta, Indonesia., 2025)
Background: Awareness of social responsibility within Islamic banking has grown rapidly in recent years, driven by increasing expectations for Islamic financial institutions to fulfill not only financial but also social and environmental obligations. This evolution reflects the growing importance of legitimacy and trust among stakeholders. Countries with a majority Muslim population, such as Indonesia, Malaysia, and the Gulf states, are expected to lead in implementing Islamic-based social responsibility practices and transparent reporting through Islamic Social Reporting (ISR) Objectives: This research aims to examine the impact of Islamic Social Reporting (ISR) disclosure on the profitability of Islamic banks in selected Organization of Islamic Cooperation (OIC) member countries. Novelty: The novelty of the study lies in its cross-country comparative analysis of ISR practices among Islamic banks within OIC member nations. While prior studies have explored the relationship between ISR and financial performance, limited research has examined how cultural, regulatory, and institutional contexts across Islamic economies shape this relationship. This study contributes to the literature by providing empirical evidence on how ISR may entail short-term trade-offs with profitability but serve as a foundation for long-term sustainability and ethical accountability. Research Methodology / Design: A quantitative research approach was employed using secondary data derived from the financial statements and sustainability reports of Islamic banks from 2021 to 2024. Data analysis involved classical assumption testing, simple linear regression to test the relationship between ISR and profitability (ROA, ROE), and one-way ANOVA to identify cross-country differences. Statistical analysis was performed using SPSS software. Findings: The findings reveal that ISR disclosure has a significant negative influence on Islamic banks’ profitability as measured by both ROA and ROE. Additionally, ISR disclosure levels vary significantly across countries, with Indonesia demonstrating higher levels compared to Malaysia and the Gulf states. These results indicate that while ISR strengthens ethical accountability and transparency, its financial benefits are not immediate but may accumulate over time. Implication: The study implies that Islamic banks must strategically balance their social and financial objectives. Theoretically, the findings support the legitimacy theory and stakeholder theory by emphasizing that socially responsible behavior enhances institutional credibility. Practically, policymakers and banking regulators should encourage standardized ISR frameworks to ensure that social responsibility reporting contributes not only to ethical governance but also to sustainable financial performance in the long term.